Total absence of the pericardium associated with hypogammaglobulinemia and bronchiectasis in a girl - Rachel Kinuani; Pierre-Julien Bruyère; Laurent Schoysman; Céline Kempeneers; Benoît Daron; Marie-Christine Seghaye (MDPI AG, 2019)
We report the case of an 8-years-old girl with recurrent pulmonary infections and wheezing since infancy, in whom asthma and immunoglobulin-G deficiency were diagnosed at the age of 7 months. Since then, the patient was treated for asthma without any satisfactory control of the disease. Cardiomegaly was finally diagnosed radiologically that led to cardiac assessment. Echocardiography suggested left sided partial anomalous pulmonary venous return that was not confirmed at angio-computed tomography scan and cardiac magnetic resonance imaging. Instead, total absence of the pericardium with relative left lung hypoplasia and left-sided bronchiectasis was diagnosed. Immune defect was confirmed. Adequate treatment by immunoglobulin supplementation and observance of the recommended care of bronchiectasis allowed favorable evolution. This case of an unusual association between an exceptional pericardial malformation and immune deficiency causing lower respiratory tract infections complicated by leftsided bronchiectasis highlights the absolute necessity to explore further any child with insufficient asthma control.